Broadcast Studio Development for Supporting Online Learning and Community Counselling - R. Wahyu Tri Hartono; Muhammad Yusuf Fadhlan; Maya Rahayu; Feni Isdaryani; Dianthika Puteri Andini (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2022)
Universities have a role and function to educate the community in addition to conducting lectures. One form of activities from this role is to provide information to the community in the form of providing guidance, sharing knowledge or training. With the advancement of internet technology today, this can be done through online platform. However, this must be supported by qualified equipment in order to gain interesting and acceptable outcomes for the community as well as students. In this service, a studio that can be used to support teaching activities and community counselling for academic community in Politeknik Negeri Bandung is created. The making of this broadcast studio is divided into three stages. The first is the making of a three-dimensional model of the room using 3D modelling software. The second stage is the civil work to build a broadcast studio. The last stage is the completion of the broadcast studio with supporting equipment for video content creation. The results obtained are quite satisfactory. From the majority of answers obtained from the survey, students find this studio useful, quite comfortable to use and worthy of creating video content. For the audio section, the correspondents believe that this aspect still needs to be improved, while the room layout and visual equipment are considered good and attractive.